The Veneration of Dayak Latok among the Chinese in Singkawang, West Kalimantan - Chai, Elena Gregoria Chin Fern (Laureate Book Co, Ltd,Taiwan, 2018)
This paper describes the worship of Dayak deity among the Chinese in Singkawang, West Kalimantan. The belief of Datuk Kong拿督公, a Malay deity is a common phenomenon among the Chinese in East and West Malaysia. Many Tua Pek Kong temples in Sarawak (East Malaysia) house one or a few subsidiary Datuk Kong deities. There are also temples devoted to Datuk Kong as its main deity in the Central region of Sarawak. However, the veneration of Latok Kong啦督公, the Dayak deity is unheard of in Sarawak and is totally confined to the neighbouring Chinese in West Kalimantan. Rituals, beliefs and symbols are constantly adapted, transformed to stabilise and cater to the emotional needs of the community. Tua Pek Kong, Datuk Kong, Latok Kong are local tutelary deities believed to protect and help its people. Thus, it is the humble aim of this ethnographic paper to provide further understanding into the reflexivity and adaptivity of Chinese folk beliefs towards its social surrounding.